At the heart of the problem: congestive cardiac failure as a cause of ascites: A narrative review. Issue 31 (5th August 2022) - Goh, Zhong Ning Leonard; Teo, Roland Yii Lin; Chung, Bui Khiong; Wong, Alexis Ching; Seak, Chen-June
Abstract : Heart failure leading to cardiac ascites is an extremely rare and underrecognized entity in clinical practice. Recognizing cardiac ascites can be difficult, especially since patients presenting with ascites may have more than 1 etiology. Various biomarkers are available to aid in the diagnosis of cardiac ascites, though with differing sensitivities and specificities. Such biomarkers include serum albumin, ascitic albumin and protein, as well as serum N-terminal pro-brain natriuretic peptide (NT-proBNP). While serum NT-proBNP is a powerful biomarker in distinguishing the etiology of ascites and monitoring treatment progression, its cost can be prohibitive in low-resource settings. Clinicians practicing under these circumstances may opt to rely on other parameters to manage their patients. We go on further to report a series of 3 patients with cardiac ascites to illustrate how these biomarkers may be employed in the management of this patient population. Clinicians should always keep in mind the differential diagnosis of cardiac failure as a cause of ascites. The resolution of cardiac ascites may serve as a surrogate clinical marker for response to antifailure therapy in lieu of NT-proBNP at resource-scarce centers.